Pattu Weaving: A Sustainable Fabric Manufacturing Technique - Srivastava, Ankita; Saxena, Ankur (Journal of Sustainability and Environmental Management, 2022)
Sustainability is the need of the hour and the world is now looking for the environment-friendly options while choosing the materials, techniques, processes and disposal systems. In textiles, handloom weaving is considered as the sustainable way of fabric manufacturing. Many ancient crafts clusters are still existing and re-inventing themselves to create sustainable products. The craft of ‘Pattu weaving’ is one of them which is known as a traditional weaving technique. Pattu weaving is a traditional craft using extra weft weaving technique which is widely practised by the weavers in India. The study has reviewed the materials, tools, techniques and processes used in this craft, along with the challenges and opportunities for the upliftment of the craft. A comparative study of traditional and contemporary materials, colour palette, motifs and product range of the craft are also covered in this paper. Major part of the information and images have been collected during craft research documentation activity while visiting the craft cluster at Bhojasar and Karwa villages in Rajasthan where Pattu craft has been practiced by the weavers since ages. Along with this, secondary research has also been included in this document to strengthen the study.